Peran Orang Tua/Wali Murid SDN Pondok Pinang 01 Pagi dalam Implementasi Kurikulum 2013 - Altoviah Nuha Belvar; Hindun Hindun (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the role played by parents or guardians of students at Pondok Pinang 01 Pagi State Elementary School (SDN) in supporting and involving themselves in the implementation of the 2013 Curriculum. The active role of parents is considered a factor in the successful implementation of this curriculum. This research use desciptive qualitative approach. Qualitative, descriptive research is a problem formulation that guides research to explore or photograph the social situation that will be studied thoroughly, broadly and in depth. The method used to obtain data is research by distributing questionnaire forms through an approach that allows researchers to collect data from respondents through written questionnaires. The results of the research show that parents are actively involved in supporting their children's learning, both through participation in learning activities at home, support for student project assignments, and through collaboration with teachers. Children who have active support and involvement from parents tend to show improved academic achievement. This support can include helping with homework, providing positive reinforcement, and motivating the child to learn.